(3MGTjI Ydi Odjd GdWGdHjf (B((3dcdGe GdfMhjjf(B)s - (3eMeO Hf MSf Hf Ydj GdOHGZs; (3eQYj GdcQej,J (B1033 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd deG cGf Yde GdfMh ef CLd GdYdhe GdCOHjI hcGfJ Gdgee QGZHI Yf GdeWhdGJ s
(3BNQgG (B:s
(3hgh Cf GdeYQH jbhd HCf GdCSeGA bHd GdJQcjH eHfjI hef PgH Edi GdKGdK hgh Cf GdeYQH s
(3GdQSGdI GdebOSjI GdeSeGIHOdjd GdWGdHjf dcdGe GdfMhjjfs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B218s
Keywords: (3GdfMhs